1996
DOI: 10.1063/1.117393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ultrafine gallium nitride powder by the direct current arc plasma method

Abstract: Superconducting properties and crystal structures of singlecrystal niobium nitride thin films deposited at ambient substrate temperature Structural investigation of two carbon nitride solids produced by cathodic arc deposition and nitrogen implantation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…At the NH 3 flow rates of 400 and 200 sccm, the hexagonal crystals were synthesized as shown in Figures 3a and b, respectively. This hexagon shape has been already reported as a typical GaN crystal (Grzegory et al 1995;Li et al 1996). The deposition was nonuniform on the Si substrate; although the amount of GaN in Figure 3a appeared smaller than that in Figure 3b, the overall amount in the sample in Figure 3a was larger than that in Figure 3b.…”
Section: Resultsmentioning
confidence: 81%
“…At the NH 3 flow rates of 400 and 200 sccm, the hexagonal crystals were synthesized as shown in Figures 3a and b, respectively. This hexagon shape has been already reported as a typical GaN crystal (Grzegory et al 1995;Li et al 1996). The deposition was nonuniform on the Si substrate; although the amount of GaN in Figure 3a appeared smaller than that in Figure 3b, the overall amount in the sample in Figure 3a was larger than that in Figure 3b.…”
Section: Resultsmentioning
confidence: 81%
“…In fact, in the past decade, more and more chemical and physical routes under moderate temperatures and pressures have been used to synthesize the high-pressure phases with the metastable structural states in the corresponding thermodynamic equilibrium diagram [206][207][208][209][210][211][212]. As described in Section 4, the thermodynamic state of high temperature, high pressure and high density created by PLA of a solid target in a liquid environment is favorable for the formation of the metastable phases.…”
Section: Diamond and Related Nanocrystalsmentioning
confidence: 99%
“…Due to excellent characteristics like high efficient and contamination-free, plasma method was an important method to synthesize GaN nanopowder using Ga metal and NH 3 /N 2 as raw materials. Li et al [6,7] had fabricated ultrafine hexagonal GaN powder with the size about 20-200nm using the dc arc plasma method. Their investigation demonstrated that the conversion of Ga metal to GaN nanopowder was determined by the mixture ration of NH 3 and N 2 in the mixture gas.…”
Section: Preparation Methods Of Gallium Nitride Powde R Ga Metal As Rmentioning
confidence: 99%